2015
DOI: 10.1097/bsd.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Management of Thoracolumbar Trauma and Postoperative Infection

Abstract: There is lack of consensus regarding the appropriate management of thoracolumbar fractures. In the future, multicenter prospective studies are necessary to establish guidelines for the management of thoracolumbar fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Additionally, certain injuries, including TL-spine burst fractures without neurological deficit, can often be managed non-operatively. 83,84 Moreover, a recent multicenter prospective randomized study in Canada revealed no benefit in short-or long-term outcomes in terms of pain relief or disability assessment in patients with incomplete TL-spine burst fractures treated with orthotic bracing versus no bracing. 85,86 Surgical intervention or orthotics traditionally define what constitutes a "clinically significant" injury.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, certain injuries, including TL-spine burst fractures without neurological deficit, can often be managed non-operatively. 83,84 Moreover, a recent multicenter prospective randomized study in Canada revealed no benefit in short-or long-term outcomes in terms of pain relief or disability assessment in patients with incomplete TL-spine burst fractures treated with orthotic bracing versus no bracing. 85,86 Surgical intervention or orthotics traditionally define what constitutes a "clinically significant" injury.…”
Section: Discussionmentioning
confidence: 99%
“…An essential role of the orthosis in the healing process of these injuries has never been proven, which explains the current subjective use in postoperative care. 2 3 The beneficial effect can only be scientifically tested by randomising groups between the use and no use of an orthosis. To our best knowledge, this is the first prospective randomised study on the use of postoperative orthoses.…”
Section: Discussionmentioning
confidence: 99%
“…Stability is a key factor in the determination of fracture treatment. Kepler et al 7 list the fracture types, in order of increasing instability, as compression, burst, flexion-distraction and fracture-dislocation.…”
Section: Stabilitymentioning
confidence: 99%